Diversity of antibiotic resistance gene variants at subsequent stages of the wastewater treatment process revealed by a metagenomic analysis of PCR amplicons - Gorecki, Adrian; Ostapczuk, Piotr; Dziewit, Lukasz (Frontiers in Genetics, 2024)
Wastewater treatment plants (WWTPs) have been recognised as point sources of various antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs), which are considered recently emerging biological contaminants. So far, culture-based and molecularbased methods have been successfully applied to monitor antimicrobial resistance (AMR) in WWTPs. However, the methods applied do not permit the comprehensive identification of the true diversity of ARGs. In this study we applied next-generation sequencing for a metagenomic analysis of PCR amplicons of ARGs from the subsequent stages of the analysed WWTP. The presence of 14 genes conferring resistance to different antibiotic families was screened by PCR.In the next step, three genes were selected for detailed analysis of changes of the profile of ARG variants along the process. A relative abundance of 79 variants was analysed. The highest diversity was revealed in the ermF gene, with 52 variants. The relative abundance of some variants changed along the purification process, and some ARG variants might be present in novel hosts for which they were currently unassigned. Additionally, we identified a pool of novel ARG variants present in the studied WWTP. Overall, the results obtained indicated that the applied method is sufficient for analysing ARG variant diversity.